Offering a Pattern of Ecotourism Management Pattern with an Emphasis on the Urban Ecological Textures (Case Study: District 9 of Isfahan’s Municipality) - Somayeh Hamsian Ettefagh; Hussein kalantari khalilabad; Muhammad Mire’ei (تحقیقات کاربردی علوم جغرافیایی)
As it can take an efficient step towards the preservation and sustainability of such lands due to the preparation, implementation, and reformation of criteria. In District 9 of Isfahan Municipality, mismanagement in the preservation of ecological lands has destroyed gardens and agricultural lands, and has caused the loss of social unity of neighborhoods. Consequently, the study of ecotourism management in this region is of great significance. For this reason, in this paper, a model for ecotourism management with an emphasis on urban ecological textures is provided for District 9 of Isfahan Municipality. For this reason, first, the Star method has been used as a model for interviewing experts and relevant municipal experts in Isfahan city management. At that point, with the help of library investigations and field assessments, and implementation of the grounded theory method, 3 dimensions, 10 categories, and 35 subcategories are extracted from the data gained from the interview. The main dimensions are urban texture management (with categories legislation, planning, management of resources and control and supervision), the ecological texture (with the categories: protection and development and improvement), ecotourism (with the economic, social, environmental and cultural categories).